Script or style? Analysis of the relationship between teaching scripts and supervision style - Julia Sader; Nadia M. Bajwa; Robin Lüchinger; Thomas Fassier; Marie-Claude Audétat; Mathieu Nendaz; Noelle Junod Perron (PLoS ONE, 2026)
Purpose Clinical teachers use both clinical and teaching scripts when supervising students. The aims of the study was: 1) to explore how teaching scripts are operationalized during supervision of clinical reasoning, and 2) to evaluate whether teaching scripts and their activation vary according to clinical teachers’ level of teaching experience. Materials and methods A purposeful sample of 20 clinical teachers from different disciplines and levels of teaching experiences were invited to conduct a videotaped clinical supervision with a simulated resident involving a patient presenting with subacute lower abdominal pain. The session was followed by a semi-structured and a stimulated recall interview. Both were transcribed and analysed using deductive and inductive approaches. Results Teaching scripts were operationalized into four clear supervision styles along two axes: the richness of the pedagogical dimension of teaching scripts and the flexibility of teaching approaches. Participants’ working context, prior clinical experience, teaching training opportunities and reflective skills seemed to determine these teaching styles. However, they did not vary according to the level of teaching experience. Conclusion The results of this study shed light on how faculty development programs can guide and enhance clinical teachers’ supervision skills based on the analysis of their existing teaching scripts and supervision styles.